The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/s19030743
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Land Subsidence in Wuhan City (China) using the SBAS-InSAR Method with Radarsat-2 Imagery Data

Abstract: Wuhan city is the biggest city in central China and has suffered subsidence problems in recent years because of its rapid urban construction. However, longtime and wide range monitoring of land subsidence is lacking. The causes of subsidence also require further study, such as natural conditions and human activities. We use small baseline subset (SBAS) interferometric synthetic aperture radar (InSAR) method and high-resolution RADARSAT-2 images acquired between 2015 and 2018 to derive subsidence. The SBAS-InSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 45 publications
(58 reference statements)
5
57
0
1
Order By: Relevance
“…This technique overcomes the low coherence of some interferograms induced by single super-master images and reduces the requirement of the quantity of SAR images with respect to PS-InSAR [29]. SBAS-InSAR is widely applied in land subsidence detection [26,27,31], and is based on the following equations [25]:…”
Section: Basic Theory Of Sbas-insarmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique overcomes the low coherence of some interferograms induced by single super-master images and reduces the requirement of the quantity of SAR images with respect to PS-InSAR [29]. SBAS-InSAR is widely applied in land subsidence detection [26,27,31], and is based on the following equations [25]:…”
Section: Basic Theory Of Sbas-insarmentioning
confidence: 99%
“…More specifically, a permanent scatterers InSAR (PS-InSAR) method proposed by Ferretti et al and a small baseline subset InSAR (SBAS-InSAR) method introduced by Berardino et al have been widely used in related fields with millimetric accuracy [23][24][25]. Zhang and Zhou analyzed Wuhan land subsidence using SBAS-InSAR, and observed four major subsidence zones affected by urban construction and industrial development [26,27]. Chaussard et al calculated land subsidence in Mexican and Indonesian cities using the SBAS-InSAR method, and found that land subsidence was directly related to the overexploitation of groundwater [2,28].…”
mentioning
confidence: 99%
“…The land subsidence starts slowly and spreads to adjacent areas, where it could affect agricultural, industrial, and urban activities. Land subsidence has been recognized as a serious environmental problem [ 5 , 6 , 7 ]. There are some strategies to monitor or control land subsidence, but if it progresses without the required supervision, the land could lose its functionality in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The following seven papers are specifically dedicated to applications. The first two [13,14] use SAR interferometry (InSAR) for investigating displacements related to land subsidence and highway deformation. Multi-temporal InSAR is a well-established technique currently applied to displacement monitoring thanks to the availability of reliable processing tools developed during the last two decades, as well as data archives continuously updated by operative satellite missions.…”
Section: Ground Displacement Monitoringmentioning
confidence: 99%
“…In [13], high-resolution RADARSAT-2 SAR data were processed through the Small BAseline Subset (SBAS) algorithm for deriving 3-year displacement time series over Wuhan city, which suffers from subsidence problems related to urban construction. First, the InSAR results were compared to measurements from levelling benchmarks for a quality check.…”
Section: Ground Displacement Monitoringmentioning
confidence: 99%